1997
DOI: 10.1007/s004410050870
|View full text |Cite
|
Sign up to set email alerts
|

Immunoelectron-microscopic investigation of the subcellular localization of pinopsin in the pineal organ of the chicken

Abstract: Pinopsin is a photoreceptive molecule cloned from the chicken pineal organ. An antibody highly specific for pinopsin was applied in light- and electron-microscopic immunocytochemical studies of the pineal organ of 1 to 2-month-old chickens. Intense immunoreactivity was found in the follicular lumen at the light-microscopic level. In addition, small immunoreactive spherical or fibrous structures were diffusely distributed at the parafollicular aspect of the pineal organ. To identify immunoreactive elements prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…In 1994, Okano et al announced the discovery of a non-visual opsin expressed in the chicken pineal (Okano et al 1994), which they named 'pinopsin.' Immunoelectron microscopic investigations by Hirunagi et al (1997) showed that pinopsin was located in the outer segments of pinealocytes, but for no species has it ever been shown to occur in the eye's retina, the structure we focus on in this article.…”
Section: Research Into Photoreceptors-'old' and 'New'mentioning
confidence: 99%
“…In 1994, Okano et al announced the discovery of a non-visual opsin expressed in the chicken pineal (Okano et al 1994), which they named 'pinopsin.' Immunoelectron microscopic investigations by Hirunagi et al (1997) showed that pinopsin was located in the outer segments of pinealocytes, but for no species has it ever been shown to occur in the eye's retina, the structure we focus on in this article.…”
Section: Research Into Photoreceptors-'old' and 'New'mentioning
confidence: 99%
“…The gland contains photoreceptor-type secretory pinealocytes that produce melatonin, interstitial cells and rare nerve cells. The pineal photopigment pinopsin [30,31] is exclusively present in the outer segments of secretory pinealocytes [32], as are the pinopsin-related G proteins [33]. Since the nerve cells do not exhibit immunoreactivity for pinopsin [32] and since photoreceptor cells are well known for not producing action potentials, we hypothesize that the cells described here are nerve cells and that their firing is influenced by the photopigment-containing pinealocytes.…”
Section: Discussionmentioning
confidence: 86%
“…The pineal photopigment pinopsin [30,31] is exclusively present in the outer segments of secretory pinealocytes [32], as are the pinopsin-related G proteins [33]. Since the nerve cells do not exhibit immunoreactivity for pinopsin [32] and since photoreceptor cells are well known for not producing action potentials, we hypothesize that the cells described here are nerve cells and that their firing is influenced by the photopigment-containing pinealocytes. In agreement with this hypothesis are the findings that the spiking cells and the nerve cells are both rare and that nerve cells have been demonstrated in the chick pineal gland as early as 3 days after hatching [34].…”
Section: Discussionmentioning
confidence: 86%
“…Three types of pineal photoreceptors have been identified immunocyto-chemically Hirunagi et al, 1997;Okano et al, 1997;Yamao et al, 1999). A previous study indicates that differentiation of rhodopsin-IR and iodopsin-IR cells is controlled by different environmental cues (Araki, 1997); conditioned medium from cerebral cortical cultures of the chick embryo considerably enhanced differentiation of rhodopsin-IR cells but had no effect on iodopsin-IR cells.…”
Section: Synergistic Effects Of Igf-1 and Egf On Pineal Photoreceptormentioning
confidence: 96%
“…The endocrinal properties of the chick pineal begin to appear only at the late stage of development (Zeman et al, 1999;Faluhelyi et al, 2005). Previous immunocytochemical studies have shown that developing pineals of the quail embryo contain three types of photoreceptors as revealed by specific antibodies against rhodopsin, iodopsin, or pinopsin Hirunagi et al, 1997;Yamao et al, 1999). Pinopsin-immunoreactive (pinopsin-IR) cells predominate, and iodopsin-IR cells and rhodopsin-IR cells are rather minor cell types.…”
Section: Introductionmentioning
confidence: 95%